Antioxidant activity and microbiological quality of bee bread collected from three different species honey bee. Issue 1 (April 2020) - Jaya, F; Rosyidi, D; Radiati, L E; Minarti, S; Mustakim,; Susilo, A; Muslimah, R H; Husolli, M
Abstract: Honeybee can produce bee bread beside the most famous commercial products i.e. honey, propolis and pollen. This product is widely believed to have medicinal benefits. However, there are very few scientific data available on the honeybee's bee bread to prove the claims. In this study, bee bread from different species honeybee, namely Apis mellifera, Apis cerana, and Trigona spp were evaluated as antioxidants agents and microbiological quality. Bee bread from Apis cerana exhibited the highest microbiological quality including total microorganism (5.58 ± 0.38 log CFU/g), total yeast (6.23 ± 0.13 log CFU/g), total LAB (3.68 ± 0.27 log CFU/g) pH (4.36 ± 0.10) and Aw (0.7200 ± 0.0008), followed by Apis mellifera and Trigona spp . Meanwhile, bee bread from Apis cerana showed the highest antioxidant activities as radical scavenger was 14.44±0.25 mg / mL, total flavonoid was 0.73±0.05 mg QE/g and total phenolic was 4.01±0.68 mg GAE/g. These findings establish the potential of bee bread from Apis cerana as antioxidants agent and microbiological quality, promising natural food supplements and natural preservatives.